Correlation between echocardiographic findings and biochemical markers in term newborns with moderate to severe perinatal asphyxia - Vasiljević, Milena; Nešić, Dejan M.; Krasić, Staša; Ninić, Sanja; Prijić, Sergej; Ašanin, Milika; Stanković, Sanja; Cerović, Ivana; Milićević, Srboljub; Knežević-Rangelov, Sanja; Vukomanović, Vladislav (Archives of Biological Sciences, 2021)
Paper description: Perinatal asphyxia is a condition characterized by a gas exchange disorder with potential multiorgan dysfunction due to a lack of blood flow or gas exchange. We determined the correlation between biochemical markers and echocardiography findings in asphyxiated neonates in comparison with control individuals. We confirmed a significant correlation between echocardiographic and biochemical parameters of the myocardial lesion and cardiac function. Due to their complementarity, the use of the biochemical and echocardiographic parameters may be conditioned by their availability. Abstract: Perinatal asphyxia (PA) is a condition characterized by a gas exchange disorder due to a lack of blood flow or gas exchange, with potential multiorgan dysfunction. Our study aimed to determine the correlation between biochemical markers and echocardiography findings in a group of asphyxiated newborns. The prospective cohort study included 120 neonates (52/120 with PA) treated at a tertial referral pediatric center, from 2012 to 2014. A moderate-strong positive correlation was recorded between the transtricuspid pressure gradient (TRPG) and serum lactate, and between TRPG and NT-proBNP in the PA group (P<0.001) on the 1st day of life. A moderate positive correlation was found between NT-proBNP, lactate and troponins on one side, and TRPG on the other in the PA group after the 2nd measurement. Multinomial regression analysis showed that the lactate level was an independent factor for survival on the 1st (odds ratio (OR) 41.3, 95% confidence interval (CI) 2.14-797.1) and 3rd (OR 136.4, 95% CI 2.27-8206.7) days. Our research confirmed a significant correlation between echocardiographic and biochemical parameters of the myocardial lesion and cardiac function. Due to their complementarity, the use of the biochemical and echocardiographic parameters may be conditioned by their availability.